Assessment of Attitudes and Barriers of Ghanaian Radiographers Towards Postgraduate Radiography Education - Ohemeng, Evan; Atinga, Ba-Etilayoo; Barima, Twum; Antwi, Lina Nyarko (British Journal of Healthcare and Medical Research, 2022)
Introduction: There has been a great evolution since X-ray was discovered. The profession has expanded with advance medical imaging techniques such as computed Tomography (CT), Magnetic resonance imaging (MRI) and a host of them. The need therefore for radiographers to upgrade their knowledge and skills cannot be over emphasized. It is therefore imperative to assess the barriers that make most Ghanaian radiographers miss out opportunities for postgraduate radiography education in Ghana. Methods: This was a mixed method study (qualitative and quantitative). Questionnaires with close and open-ended questions were employed as the data collection technique and Purposive sampling technique was used in the questionnaire administration. Results: It was identified that 86.4% of the total respondents being aware of postgraduate radiography education opportunities in Ghana. 88% were willing to enroll in postgraduate radiography education and 76% willing to self- fund their postgraduate education. 170 responses were received from the questionnaire for this study giving a response rate of 70%. Seventy seven percent of respondents were males whiles 23% were females. Conclusion: The study has shown that Ghanaian radiographers have a positive attitude towards postgraduate radiography education and have enthusiasm to self-sponsorship. However, factors such as high cost of postgraduate education, lack of funding, aging and increase responsibility of radiographers’ content against radiographers’ postgraduate education.